The Plasmodium berghei RC strain is highly diverged and harbors putatively novel drug resistance variants - Songsungthong, Warangkhana; Kulawonganunchai, Supasak; Wilantho, Alisa; Tongsima, Sissades; Koonyosying, Pongpisid; Uthaipibull, Chairat; Kamchonwongpaisan, Sumalee; Shaw, Philip J. (PeerJ, 2017)
Background The current first line drugs for treating uncomplicated malaria are artemisinin (ART) combination therapies. However, Plasmodium falciparum parasites resistant to ART and partner drugs are spreading, which threatens malaria control efforts. Rodent malaria species are useful models for understanding antimalarial resistance, in particular genetic variants responsible for cross resistance to different compounds. Methods The Plasmodium berghei RC strain (PbRC) is described as resistant to different antimalarials, including chloroquine (CQ) and ART. In an attempt to identify the genetic basis for the antimalarial resistance trait in PbRC, its genome was sequenced and compared with five other previously sequenced P. berghei strains. Results We found that PbRC is eight-fold less sensitive to the ART derivative artesunate than the reference strain PbANKA. The genome of PbRC is markedly different from other strains, and 6,974 single nucleotide variants private to PbRC were identified. Among these PbRC private variants, non-synonymous changes were identified in genes known to modulate antimalarial sensitivity in rodent malaria species, including notably the ubiquitin carboxyl-terminal hydrolase 1 gene. However, no variants were found in some genes with strong evidence of association with ART resistance in P. falciparum such as K13 propeller protein. Discussion The variants identified in PbRC provide insight into P. berghei genome diversity and genetic factors that could modulate CQ and ART resistance in Plasmodium spp.
Keywords: Plasmodium berghei RC; Artemisinin; Malaria; Genome; Chloroquine